Sex, communism, and videotapes: Polish sexual (r)evolutions, 1956-1989 - Dobrowolska, A (2021)
The thesis investigates the history of state-socialist sexualities in Poland through the lens of visual culture. By focusing on phenomena such as striptease shows, nude photography exhibitions, beauty pageants, and pornographic videotapes, the thesis examines the changing approaches toward nudity and sex in Polish public discourse between 1956 and 1989. Thus, the dissertation seeks to uncover the forgotten history of state-socialist sexual (r)evolutions and engages critically with the scholarship on the global sexual revolution to complicate our understanding of this phenomenon beyond the usual Cold War stereotypes. Methodologically, this dissertation focuses on the role sexuality played in dominant discourses that attempted to redefine, modernise, and control both male and female bodies. Inspired by Michel Foucault’s approach to the history of sexuality, this thesis focuses on discourse and perceives it as a primary field in which sexuality, norms, and transgressions of norms are constructed and defined. The dissertation surveys a wide array of sources – from official documents, through articles printed in popular press, up to the first sexualised advertisements. On the one hand, the thesis focuses on the role of communist ideology and official regulations in creating space where new sexual identities could emerge, as well as in limiting their scope. On the other, it also analyses the role consumerist aspirations played in modernising sexual behaviours toward the end of state socialism and how sexuality came to be used as a metaphor to narrate the sense of late state-socialist crisis. In many regards the ‘Eastern’ example teaches us that sexual liberation is not a straightforward and one-dimensional process but, rather, that it can denote quite different things depending on its geographical and social context.